(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This article analyzes the works of the great English writer of the 20th century, Herbert Wells, and talks about the genre features and process of creating his works. Also, the novel genre and its features, which are the most used in English literature of the 20th century, are covered. Herbert Wells is best known for his science fiction and social fiction novels.